Does an increased probability of graft‐vs‐host disease improve the survival of patients with adult T‐cell leukemia‐lymphoma? A simulation analysis using a Markov model. Issue 3 (10th April 2019) - Fuji, Shigeo; Kurosawa, Saiko; Inamoto, Yoshihiro; Nakano, Nobuaki; Miyazaki, Yasuhiko; Miyashita, Kaname; Hidaka, Michihiro; Eto, Tetsuya; Uchida, Naoyuki; Ito, Asahi; Sawayama, Yasushi; Miyamoto, Toshihiro; et al.
Abstract: Adult T‐cell leukemia‐lymphoma (ATL) is a peripheral T‐cell lymphoma caused by human T‐cell lymphotropic virus type I. Previous retrospective studies suggested the presence of graft‐vs‐ATL (GV‐ATL) effects associated with acute graft‐vs‐host disease (GVHD), which suggests that intentional induction of acute GVHD to facilitate the efficacy of GV‐ATL effects might reduce the risk of relapse and contribute to improved survival after allogeneic hematopoietic stem cell transplantation. However, it is impractical to conduct a prospective study to assess the benefit of intentional induction of acute GVHD. In a simulation analysis using a Markov model, we assessed the impact on overall survival (OS) of changing the probability of overall acute GVHD and severe acute GVHD. When the probability of grade III‐IV acute GVHD changed from 0% to 100%, the expected 2‐year OS rate changed from 57.0% to 21.8% (48.2% of baseline at 2 years). When the probability of all grades of acute GVHD changed from 0% to 100%, the expected 2‐year OS rate changed from 48.2% to 49.5%. In conclusion, increasing the probability of overall acute GVHD was beneficial only when the proportion of grade III‐IV acute GVHD was lower than that in the original data. Based on the simulation results, preventive management of grade III‐IV acute GVHD is mandatory to achieve the clinical benefit associated with grade I‐II GVHD.